ANALISA STRATEGI PANETRASI PASAR DALAM RANGKA MENINGKATKAN PANGSA PASAR LBPP LIA PADANG - Putri, Eka Risma (jurnal ekonomi, 2007)
Market penetration strategy is a strategy that conduction by a company in order to increase markete potency for its product and market that available through more agresive marketing efforts. Effort of market's penetrating strategy that can be done for example; stimulating consumens to increase their purchassing, influencing competitor's consumen and attrack the consumen candidate that is non-user. In this case, the choosen penetrating strategy is rapid penetration, wich is this strategy using cheap pricing or reached with activity of high promotion. This strategy has to be supported with intensive marketing mix.